2022
DOI: 10.1037/per0000483
|View full text |Cite
|
Sign up to set email alerts
|

We are who we thought we were: Confirming one’s own antagonism levels.

Abstract: Although many processes might contribute to the self-perpetuating nature of antagonistic personality, we proposed and tested the "antagonism-confirmation" perspective on this phenomenon. This perspective states that antagonistic personality is based in tendencies to confirm (vs. disconfirm) the self's beliefs about its personality. Importantly, this explanation uniquely predicts that antagonism-related personality constructs should relate to strategically adopting behaviors that vary on only their significatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 87 publications
0
9
1
Order By: Relevance
“…That is, there was no clear evidence that people relatively higher in sadism were any less likely to use the framing manipulations to seem more moral (Study 1) or less antagonistic (Study 2). Hence, on the surface, the present data call into question findings in Hart, Richardson, et al (2022) that supported antagonism confirmation; recall that more antagonistic participants in that study used their perceptions of color change on a bogus color-gazing task to signal an antagonistic identity. However, it is possible to reconcile the discrepant evidence.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…That is, there was no clear evidence that people relatively higher in sadism were any less likely to use the framing manipulations to seem more moral (Study 1) or less antagonistic (Study 2). Hence, on the surface, the present data call into question findings in Hart, Richardson, et al (2022) that supported antagonism confirmation; recall that more antagonistic participants in that study used their perceptions of color change on a bogus color-gazing task to signal an antagonistic identity. However, it is possible to reconcile the discrepant evidence.…”
Section: Discussionmentioning
confidence: 66%
“…Prior antagonism confirmation research observed cross-over interactive effects that were moderate in size (f 2 = 0.09; Hart, Richardson, et al, 2022); however, the present work took a more conservative approach to estimating the interaction. Similar to prior conceptually related research (see Hart, Tortoriello, et al, 2021;Kwang & Swann, 2010), we estimated that the simple slope of sadism in each experimental condition would be on par with average effect sizes in individual difference research (r = 0.20 when displeasure is moral; r = −0.20 when sadistic pleasure is moral; Gignac & Szodorai, 2016).…”
Section: Participantsmentioning
confidence: 81%
See 3 more Smart Citations